The Effect of Environmental Accommodations on Attending Behavior of an ADHD Chapter I Student An Action Research Study - Greenewald, M. Jane.; Walsh, Cheryl ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1996)
An attention deficit hyperactivity disorder (ADHD) student's impulsivity and inattentiveness were interfering with his learning and that of his classmates. Prior to experimental intervention, a simple event recording was conducted over nine class periods to determine the frequency of this subject's impulsivity and inattentiveness. For ease of observation the most frequently occurring behavior was targeted for study. An ABAB reversal design was used to study the effects of regular instructional procedures (baseline) and instructional procedures recommended for ADHD children (intervention) on the subject's non-attending behavior. Baseline and intervention differed in terms of physical design, management, and curriculum and lesson presentation. Results indicated that the intervention did positively influence the subject's ability to attend. Because this experiment included multiple elements, further research will be needed to ascertain whether a smaller array of environmental variables or perhaps a single variable can produce similarly significant reductions in problem behaviors as quickly. It is also recommended that examination of holistic modifications of classroom environments be conducted over a longer time frame, as research indicates that behavioral problems may increase as length of exposure to a particular setting or task increases. Results of this study may serve to encourage teachers faced with the challenge of ADHD children to learn more about this disorder and to experiment with instructional strategies with the potential to create a workable match between the ADHD child's needs and the classroom environment. Contains 15 references. (TS)
ERIC Note: Paper presented at the Annual Meeting of the American Educational Research Association (77th, New York, NY, April 8-12, 1996).
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Attention; Attention Deficit Disorders; Attention Span; Behavior Disorders; Classroom Environment; Educational Environment; Hyperactivity; Learning Disabilities; Learning Problems; Neurological Impairments; Primary Education; Speeches/Meeting Papers; Reports, Research